2013
DOI: 10.1166/jnn.2013.8123
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cells Assembled with Composite Gel Polymer Electrolytes Containing Nanosized Al<SUB>2</SUB>O<SUB>3</SUB> Particles

Abstract: Polymeric ionic liquid, poly(1-methyl 3-(2-acryloyloxy propyl) imidazolium iodide) (PMAPII) containing iodide ions is synthesized and used as a matrix polymer for preparing the composite polymer electrolytes. The composite gel polymer electrolytes are prepared by utilizing PMAPII, organic solvent containing redox couple and aluminum oxide nanoparticle for application in dye-sensitized solar cells (DSSCs). PMAPII is highly compatible with organic solvents and thus there is no phase separation between the PMAPII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…25 Hence, photocurrent and efficiency will be enhanced. Recently, comparative studies of TiO 2 and SiO 2 within the polymer electrolyte have been reported by Tiautit et al It is reported that the charge transfer resistance and diffusion resistance of TiO 2 incorporated electrolyte is very lesser than SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…25 Hence, photocurrent and efficiency will be enhanced. Recently, comparative studies of TiO 2 and SiO 2 within the polymer electrolyte have been reported by Tiautit et al It is reported that the charge transfer resistance and diffusion resistance of TiO 2 incorporated electrolyte is very lesser than SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…have been used as fillers in electrolytes for dye-sensitized solar cell applications [27][28][29][30][31][32][33][34][35][36][37][38]. Among them, TiO 2 nanoparticles are considered as one of the most promising fillers because of their availability in nature, UV resistance, photocatalytic activity for pollutant removal, photoelectrochemical conversion, and anti-bacterium properties and polymorph crystalline structures like anatase, brookite, and rutile [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, modified SiO 2 nanoparticles have resulted in good solvency for inorganic salt to better dissolve within the polymer electrolytes. Other work by Jeon and Kim added aluminum oxide (Al 2 O 3 ) in a synthesized polymeric ionic liquid, poly­(1-methyl 3-(2-(acryloyloxy)­propyl)­imidazoliumiodide) (PMAPII), improve the electrolytic characteristics. The reported results revealed that the DSSC-based composite gel polymer electrolytes containing 10 wt % Al 2 O 3 nanoparticles exhibited a relatively high conversion efficiency of 6.51% at 100 mW cm –2 and better stability.…”
Section: Available Alternatives: Polymer Electrolytesmentioning
confidence: 99%